2012
DOI: 10.1017/thg.2012.33
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Delivery and Outcomes of Very Preterm Twins Stratified to Zygosity

Abstract: The increasing rates of preterm birth among twins implicate that solid data on associated risks and outcomes are required. Assessment of zygosity is often based on clinical criteria (evaluation of placenta; same gender, birth weight discordance as surrogate criteria for monochorionic/monozygotic twins). The aim of this study was to compare clinical versus genetic assessment of zygosity and to compare causes of preterm delivery as well as outcome data of very-low-birth-weight (VLBW; birth weight <1,500 g) twins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
6
0
2
Order By: Relevance
“…This raises the concern that multiplicity in the preterm subjects may have confounded our results. There is limited information on how the immune system differs with multiple births: it has been shown that intrauterine infection occurs more often in preterm births with dizygotic twins compared to monozygotic twins or singletons, but no differences in postnatal outcome have been associated with zygosity [52]. Additionally, CD4 + T cell activity has been observed to be significantly lower in preterm dizygotic twins than in preterm singletons [53].…”
Section: Discussionmentioning
confidence: 99%
“…This raises the concern that multiplicity in the preterm subjects may have confounded our results. There is limited information on how the immune system differs with multiple births: it has been shown that intrauterine infection occurs more often in preterm births with dizygotic twins compared to monozygotic twins or singletons, but no differences in postnatal outcome have been associated with zygosity [52]. Additionally, CD4 + T cell activity has been observed to be significantly lower in preterm dizygotic twins than in preterm singletons [53].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, monozygotic twins are even more frequently associated with complications, mainly because of twin-twintransfusion-syndrome (TTTS) appearance, while a higher rate of intrauterine infections have been observed among dizygotic pregnancies. 33 The incidence of twining has been estimated to approximately 1 in 65 live births, with the proportion of dizygotic twins being settled to 70%, and monozygotic to 30%. 34 Assessment of zygosity is routinely based on sonographic identification of chorionicity and fetal gender determination, while in cases when the invasive procedure was conducted, a genetic determination using STR markers could be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis is in accordance with previous studies that documented higher levels of Th2-cytokines in the blood of mothers carrying twins compared with singleton pregnancies [24] underlining the more profound Th1-Th2 shift that occurs in twin pregnancies. Moreover, a recent study demonstrated that both dizygotic twins and their mothers are more prone to infection than monozygotic twins, singletons, and their mothers [25]. …”
Section: Discussionmentioning
confidence: 99%